Influence of radiation exposure pattern on the bone injury and osteoclastogenesis in a rat model - Zhai, Jianglong (Int J Mol Med, 2019)
Radiotherapy, one of the clinical treatments of cancer, is accompanied by a high risk of damage to healthy tissues, such as bone loss and increased risk of fractures. The aim of the present study was to establish a rat model of local and systemic bone injury by focal irradiation, in order to study the etiological mechanism and intervention. The proximal metaphyseal region of the left hindlimb of male Sprague-Dawley rats were exposed to a single 2 Gy or three 8 Gy doses delivered on days 1, 3 and 5 using a small animal irradiator, the changes in bone volume and microarchitecture were evaluated, and the mineral apposition rate (MAR) was assessed. Furthermore, bone marrow-derived macrophages (BMMs) were isolated and induced to osteoclasts. It has been demonstrated that a single dose of 2 Gy may result in a significant loss of lumbar bone density at 3 days post-irradiation, however this is restored at 30 days post-irradiation. In the 3x8 Gy irradiation rat model, there was a rapid decrease in the aBMD of lumbar spine at 3 days and at 7 days post-irradiation, and the aBMD decline persisted even at 60 days post-irradiation. In addition, microCT analysis revealed a persistent decline in bone volume and damage in microarchitecture in the 3x8 Gy irradiation model, accompanied by a decrease in MAR, index of the decline in bone-forming ability. In the cellular mechanism, a single 2 Gy local irradiation mainly manifested as an enhancement of the BMMs osteoclastogenesis potential, which was different from the osteoclastogenesis inhibition after high-dose focal irradiation (3x8 Gy). In summary, the irradiation with simulated clinical focal fractionated radiotherapy exerts short- and long-term systemic injury on bone tissue, characterized by different osteoclastogenesis potential between the high dose mode and a single 2 Gy focal irradiation. Physicians must consider the irreversibility of bone damage in clinical radiotherapy.